2012
DOI: 10.3329/jssmc.v4i1.11999
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Antimicrobial Sensitivity Pattern of Extended Spectrum β-Lactamases Producing Escherichia coli and Klebsiella pneumoniae Isolated from urine at a Tertiary Care Hospital

Abstract: Background: Infections due to extended spectrum β-lactamases (ESBL) producing Escherichia coli and Klebsiella pneumoniae have become an important clinical problem. These organisms are important regarding the infection control by the physicians. Objective: The present study was undertaken to determine the prevalence of ESBLs along with their antimicrobial sensitivity pattern in Escherichia coli and Klebsiella pneumoniae. Methodology: This cross sectional study was conducted in the Department of Microbiology at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The isolates of P. vulgaris showed resistance in 100% of the cases, but this result must be taken conditionally due to the small number of isolates. This is consistent with the results from other Eastern European countries [63][64][65] , and in contrast with those from Asian countries 59,66 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The isolates of P. vulgaris showed resistance in 100% of the cases, but this result must be taken conditionally due to the small number of isolates. This is consistent with the results from other Eastern European countries [63][64][65] , and in contrast with those from Asian countries 59,66 .…”
Section: Resultssupporting
confidence: 92%
“…Results of the present study are consistent with those from the literature highlighting that prevalence of ESBL strains of K. pneumoniae is significantly higher than that of E. coli, in the European countries and USA [55][56][57][58] . The situation is reversed in the countries of Asia, Africa and South America 43,46,59,60 .…”
Section: Resultsmentioning
confidence: 99%
“…Our study showed a susceptibility of 100% for imipenem, this frequency was similar with other studies in which susceptibility varied from 95 up to 100% for imipenem. 18,20,25,30,31,36 We have few options for treating severe infections because of the significant rise in b-lactamase production, which includes the high level of ESBL producers. In this study, the ESBL strains showed high resistance to ampicillin (100%), aztreonam (78.5%), cefepime (100%), ceftriaxone (86.6%), tetracycline (66.66%), norfloxacin (50%) and nitrofurantoin (8.33%), which is consistent with a claim made by Cristea et al in Romania.…”
Section: Discussionmentioning
confidence: 99%